2020
DOI: 10.1001/jama.2020.3833
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Transcutaneous Magnetic Stimulation for Ventricular Tachycardia Storm

Abstract: Conflict of Interest Disclosures: Dr Greub reported having ongoing research agreements with Resistell and Becton-Dickinson and being medical advisor for Resistell; he also reported being developer of a card game on microbes and funding JeuPro, a start-up company that distributes the game Krobs. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Unlike the sympathetic regulation methods described above, indirect regulation methods require the placement of “receptors” inside or on the surface of the body that can sense specific external stimulus, and then the use of external energy such as electromagnetic fields (EMF) to signal to the “receptors,” and the “receptors” then exert their effects on neural activity. Transcranial EMF stimulation has been used to treat a variety of neurological disorders such as depression ( 196 ), Wang et al ( 197 ) found that intermittent low-frequency EMF stimulation of the left stellate ganglion (LSG) significantly reduced the incidence of VAs after myocardial ischemia in an animal model, and the first-in-man application of low-frequency EMF stimulation was described in a subsequent series of case reports ( 198 ), which included 5 patients with sympathetic electrical storms who had failed to respond to pharmacological treatment, the electromagnetic coil was placed on the surface of the seventh cervical spine near the LSG, and intermittent low-frequency EMF stimulation was administered, showing a significant reduction in the incidence of VAs and no device-related AEs. The STAR-VT study (NCT04043312) on low-frequency EMF stimulation for sympathetic electrical storm is ongoing.…”
Section: Other Regulation Methodsmentioning
confidence: 99%
“…Unlike the sympathetic regulation methods described above, indirect regulation methods require the placement of “receptors” inside or on the surface of the body that can sense specific external stimulus, and then the use of external energy such as electromagnetic fields (EMF) to signal to the “receptors,” and the “receptors” then exert their effects on neural activity. Transcranial EMF stimulation has been used to treat a variety of neurological disorders such as depression ( 196 ), Wang et al ( 197 ) found that intermittent low-frequency EMF stimulation of the left stellate ganglion (LSG) significantly reduced the incidence of VAs after myocardial ischemia in an animal model, and the first-in-man application of low-frequency EMF stimulation was described in a subsequent series of case reports ( 198 ), which included 5 patients with sympathetic electrical storms who had failed to respond to pharmacological treatment, the electromagnetic coil was placed on the surface of the seventh cervical spine near the LSG, and intermittent low-frequency EMF stimulation was administered, showing a significant reduction in the incidence of VAs and no device-related AEs. The STAR-VT study (NCT04043312) on low-frequency EMF stimulation for sympathetic electrical storm is ongoing.…”
Section: Other Regulation Methodsmentioning
confidence: 99%
“…They showed that this strategy significantly decreased left stellate ganglion activity and reduced myocardial infarction-induced ventricular arrhythmia burden. Markman et al [187] published a case series on five patients suffering from ventricular tachycardia storm (≥ 3 episodes of sustained ventricular tachycardia in 24 h), which were all treated with transcutaneous magnetic stimulation of the left stellate ganglion. This strategy successfully lowered arrhythmia burden and was not associated with any adverse events, further highlighting the potential of this modality to serve as a bridge to more permanent interventions.…”
Section: Emerging Modalities Of Neural Modulationmentioning
confidence: 99%
“…Also in the setting of recurrent ventricular arrhythmias, inflammatory processes were active in stellate ganglia, which might imply that microglia and other inflammatory cells contribute to this pathological phenotype. Though the role of microglia in ventricular arrhythmogenesis has been scarcely studied, Wang et al 187 [ 97 ] used a post-infarct murine model to demonstrate their involvement in ventricular arrhythmogenesis. In their study, microglial activation was inhibited through light-emitting diode (LED) illumination, a fairly new non-thermal method that modulates cellular activity through photons that are absorbed by mitochondrial chromophores [ 98 ].…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic stimulation has been shown to modify arrhythmia risk by targeting cardiac sympathetic innervation in animal models . We had previously performed a feasibility study of TcMS in patients with VT storm, which demonstrated a lower burden of VT with no adverse events . This double-blind, randomized pilot study was conducted to characterize the effects of a single session of TcMS for patients with VT storm.…”
Section: Introductionmentioning
confidence: 99%